Analisis Potensi Perangkap Baki Kuning dalam Pengendalian Hama Ramah Lingkungan pada Budidaya Jamur Tiram - Hidayat, Syarif; Trimo, Lucyana Trimo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Pests are one of the limiting factors that can reduce the productivity of oyster mushroom (Pleurotus ostreatus) cultivation. This pest attack can reduce yields by up to 49 percent. Insecticides used to control this pest are often ineffective.  Some pests which attack oyster mushrooms are easily to resistant. The use of insecticide can also reduce the productivity of oyster mushrooms because some of insecticides have antifungal activity. The possibility of insecticide residue content in the harvest is also quite high. One alternative to reduce this effect is  yellow pan trap used. This research aims to determine the effect of wáter yellow pan traps used on oyster mushroom cultivation  to pest attacks and additonal income. The research results showed that the use of yellow pan traps resulted in decreasing of pest attacks on oyster mushrooms by 15%, reducing crop damage by 13.74%, and yield quality increase by 24.06%. The increasing the yield quality can increase the income of mushroom farmers by IDR 3,317,750.00 or 18.74%. Based on these results, the use of yellow pan traps has high potential to be used as an alternative of synthetic insecticides in controlling pest attacks on oyster mushroom cultivation. These results also show that yellow pan traps can support the implementation  of organic oyster mushroom cultivation.